Comparação de sistemas de geração de energia utilizando gerador a Diesel e painéis fotovoltaicos para áreas rurais isoladas - Schneider, Francielle Pareja (2019)
With the technological development, more and more electricity-dependent equipments are used, and in isolated rural areas, even if the production of energy uses photovoltaic panels, this generated energy needs to be stored for the use. The study aimed to assess and compare the cost of some energy generation and storage systems considered to be more adequated and accessible for use in isolated rural areas without access the energy distribution network. The energy generation was performed by a Diesel generator, and by an isolated photovoltaic system, capable of supplying the same load established for the property. The energy storage, coupled to the photovoltaic system, was carried out by a bank of acid lead batteries (storage in the form of electrochemical energy). It was considered that residences consume, on average, 300 kWh of electricity per month, using a single-phase power system, in a 220 V between phase and neutral. The residence has a maximum power demand of 8 kW. Then, the system of energy storage (electrochemical batteries) was designed to deal the demands of the residence for a period of 3 consecutive days, the systems should be able to storage in total of 30 kWh energy. For the generation of energy were compared: Diesel generation and photovoltaic generation. It was observed that with the annualization of the production costs and obtaining the unit cost of production of the generator reached a cost per kWh of 2.18 already for the photovoltaic generation system, standardizing the annual disbursements and the investment was obtained a unit cost of production of the photovoltaic generator of 9.8 R $ / kWh. "This study was financed in part by the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior - Brasil (CAPES) - Finance Code 001".